2006
DOI: 10.1242/jeb.02171
|View full text |Cite
|
Sign up to set email alerts
|

Spectral sensitivity of the two-spotted gobyGobiusculus flavescens(Fabricius): a physiological and behavioural study

Abstract: SUMMARY Microspectrophotometry of Gobiusculus flavescens photoreceptors revealed a single rod visual pigment (λmaxat 508 nm) and the three cone pigments (λmax 456, 531 and 553 nm). The cone population was dominated by identical double cones containing the middle-wave-sensitive (MWS)pigment, but with a small number of non-identical MWS/LWS(long-wave-sensitive) and identical LWS double cones. Small populations of large single cones also contained either the MWS or LWS pigment. The short-wave-sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 48 publications
0
33
0
Order By: Relevance
“…The latter value is reasonable in oceanic water at low chlorophyll a levels for 550 nm (see Mobley 1994), the spectral range where fish eyes are most sensitive (e.g., Gobiusculus flavescens [Utne- Palm and Bowmaker 2006]). …”
Section: Foraging Modelmentioning
confidence: 86%
“…The latter value is reasonable in oceanic water at low chlorophyll a levels for 550 nm (see Mobley 1994), the spectral range where fish eyes are most sensitive (e.g., Gobiusculus flavescens [Utne- Palm and Bowmaker 2006]). …”
Section: Foraging Modelmentioning
confidence: 86%
“…Coastal species have visual pigments with peak absorption in the green part of the spectrum, while the pigments of oceanic and deepwater fish have peak absorption in the blue (Denton and Warren 1956;Munz and McFarland 1977). Studies have shown that a small shift in the peak wavelength of the available light can have significant effects on prey detection (Utne-Palm and Bowmaker 2006).…”
Section: Visual Food-search Behaviourmentioning
confidence: 99%
“…The visual contrast hypothesis , however, offers an attractive alternative for fish in the stenospectral zone. Many marine fishes possess photoreceptors with sensitivities extending into the long-wavelength part of the ambient spectrum, including families with many fluorescent representatives such as wrasses [40], pipefish [41] and gobies [8,42]. Hence, such species seem ideally adapted to use and perceive red fluorescence, as already suggested for the neon pygmy goby [8] and shown experimentally in the fairy wrasse Cirrhilabrus solorensis [43].…”
Section: Introductionmentioning
confidence: 98%